2010
DOI: 10.1182/blood-2009-07-234229
|View full text |Cite
|
Sign up to set email alerts
|

Wide diversity of PAX5 alterations in B-ALL: a Groupe Francophone de Cytogénétique Hématologique study

Abstract: PAX5 is the main target of somatic mutations in acute B lymphoblastic leukemia (B-ALL). We analyzed 153 adult and child B-ALL harboring karyotypic abnormalities at chromosome 9p, to determine the frequency and the nature of PAX5 alterations. We found PAX5 internal rearrangements in 21% of the cases. To isolate fusion partners, we used classic and innovative techniques (rolling circle amplification-rapid amplification of cDNA ends) and single nucleotide polymorphism-comparative genomic hybridization arrays. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 21 publications
6
105
0
Order By: Relevance
“…Li et al (14) showed that miR-17∼92 targets TGFßR2 to induce cell proliferation (14). TAOK1 was found to be a fusion partner of PAX5 in B-cell acute lymphoblastic leukemia (15). Abcc3 is a member of the ABC transporter family and is involved in drug transport or redistribution of imatinib and dasatinib anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (14) showed that miR-17∼92 targets TGFßR2 to induce cell proliferation (14). TAOK1 was found to be a fusion partner of PAX5 in B-cell acute lymphoblastic leukemia (15). Abcc3 is a member of the ABC transporter family and is involved in drug transport or redistribution of imatinib and dasatinib anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by others and ourselves found that the PAX5 gene was rearranged to at least 20 partner genes in pediatric ALL samples. 1,[29][30][31][32][33] Each of these fusion genes retains the DNA-binding paired domain, but lacks the transcriptional activation domain of the PAX5 gene. The fusion proteins may bind to promoter regions of PAX5 target genes but probably do not have transcriptional activity, thus acting as dominant negative molecules preventing Bcell differentiation by wild-type PAX5.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic analysis of bone marrow samples was performed by standard methods and FISH as described 8 (supplemental Methods, supplemental Figure 1). …”
Section: Fishmentioning
confidence: 99%